2019
DOI: 10.1037/trm0000183
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of abuse by religious authorities: A review.

Abstract: Sexual abuse by clergy has been the subject of expanding interest in recent decades, although most publications have been theoretical or descriptive rather than empirical. After a search identifying all published empirical articles focused on consequences to the victims of abuse by religious authorities (SARA), we identified recurrent themes that predominated the research, presenting the data meta-analytically when possible. The recurrent themes found in the literature were as follows: SARA in the Catholic Chu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…One clear implication of our results is the need to include the Catholic identity and all of its features in the therapeutic setting (Collins et al, 2014), due to the unique betrayal reported by its victims. More research investigating sexual abuse in other religions and denominations and comparing the outcomes with both Catholic survivors and the general population is needed (McGraw et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One clear implication of our results is the need to include the Catholic identity and all of its features in the therapeutic setting (Collins et al, 2014), due to the unique betrayal reported by its victims. More research investigating sexual abuse in other religions and denominations and comparing the outcomes with both Catholic survivors and the general population is needed (McGraw et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding our first hypothesis, and similar to observations made in studies carried out in other European countries (Dressing et al, 2021; Langeland et al, 2015; Rassenhofer et al, 2015), CSA-Church victims were predominantly males (Terry, 2008), who were abused mainly by priests or pastors. Some authors have explained this result by referring to the ease with which the clergy have had access to men/boys in their daily activity, as well as aspects related to homosexuality (McGraw et al, 2019). However, other authors have minimized the focus on this difference and argued that female victims have not yet come forward publicly and therefore there is a bias toward a higher frequency of male victims (see a review of all these aspects in Van Wormer & Berns, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rejection of variations in sexual orientation and gender identity by some religious institutions predict mental health problems (Sowe et al, 2017). The prevalence of abuse by clergy which has increasingly come to light, can also contribute to increased lifetime incidence of psychological problems and “loss of faith in God and the Church” (McGraw et al, 2019, p. 242).…”
Section: Religion and Spirituality Are Important Forms Of Multicultur...mentioning
confidence: 99%
“…Given the small number of empirical articles upon which hypotheses can be based, the qualitative and case study literature (together with the empirical examinations) were assessed for themes by McGraw, Ebadji, Dalenberg, and Wu (2018). One such pervasive theme is the effect of abuse on the victim's relationship to religion (Frawley-O'Dea, 2007).…”
mentioning
confidence: 99%
“…A third theme in many qualitative or case reports was the finding that children who were alienated and in conflict with their guardians might turn to the priests as a source of guidance. McGraw et al (2018) noted that disbelief by parents and alienation from them was a common issue noted by clinical commentators. Motivated perpetrators may also be looking for children who are alienated, hoping to more easily form a bond that would not be threatened by disclosure.…”
mentioning
confidence: 99%